Strategi kepala sekolah dalam pengembangan kompetensi profesional guru untuk meningkatkan mutu pendidikan - Wimbawarni, Wiwik; Sutanto, Agus; Dacholfany, Ihsan (JOURNAL OF INTERDISCIPLINARY SCIENCE AND EDUCATION, 2021)
Professional competence is the ability to master material broadly and deeply, and guide students by meeting the competency standards set in national education standards. Competencies that must be met include 4 competencies, namely: a. Pedagogical competence; b. Personality competence; c. Professional competence; and D. Social Competence. More detailed provisions are set out in Permendiknas No. 16 of 2007 concerning AcademicQualifications and Teacher Competencies. Regarding the work of teachers explained in Law No. 14 of 2005 article 1 as follows: "The teacher is a professional educator with the main task of educating, teaching, guiding, directing, training, evaluating, and evaluating students". This provision is certainly a reference for teachers who hold the title and are eligible with professional status. Efforts made by the principal have the aim to develop the quality of education in schools through the implementation of school programs. The quality of education is dynamic and can be examined from various perspectives. Agreement on the concept of quality is returned to the reference formulation or existing references such as educational policies, teaching and learning processes, curriculum, infrastructure, learning facilities and education personnel in accordance with the agreement of the parties concerned. The quality of education is not only determined by the school as a teaching institution, but also adjusted to what the views and hopes of the communitytend to always develop along with the progress of the times.